1992
DOI: 10.1055/s-0038-1646338
|View full text |Cite
|
Sign up to set email alerts
|

Use of Low Molecular Weight Heparin in Pregnancy

Abstract: SummaryIn a controlled study of 15 pregnant patients undergoing therapeutic termination of pregnancy, seven received subcutaneously 5,000 anti-FXa units of low molecular weight (LMW) heparin 15 and 3 h prior to the termination, and eight patients acted as controls. Paired maternal and fetal blood samples were taken (before or immediately after the termination) for assay of heparin activity by a chromogenic anti-FXa method sensitive to levels of 0.02 anti-FXa U/ml. LMW heparin was detected in all maternal sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 23 publications
4
95
0
4
Order By: Relevance
“…Alcanzan su nivel máximo a las 4 horas durante el embarazo (33,34), con una vida media de 4 a 5 horas (35). Se monitorizan mediante la cuantificación de niveles de antifactor Xa, no poseen traspaso placentario (26,36,37) y no se les asocian efectos adversos fetales (38). Tienen mayor actividad contra el factor Xa, y se unen menos a proteínas plasmáticas, células endoteliales y macrófagos, con lo que aumentan su biodisponibilidad, vida media y actividad anticoagulante.…”
Section: Tabla I Indicaciones De Distintos Niveles De Anticoagulaciónunclassified
“…Alcanzan su nivel máximo a las 4 horas durante el embarazo (33,34), con una vida media de 4 a 5 horas (35). Se monitorizan mediante la cuantificación de niveles de antifactor Xa, no poseen traspaso placentario (26,36,37) y no se les asocian efectos adversos fetales (38). Tienen mayor actividad contra el factor Xa, y se unen menos a proteínas plasmáticas, células endoteliales y macrófagos, con lo que aumentan su biodisponibilidad, vida media y actividad anticoagulante.…”
Section: Tabla I Indicaciones De Distintos Niveles De Anticoagulaciónunclassified
“…The risk of osteoporosis is lower in pregnant women treated with LMWH than with UFH [166]. Insertion of a vena caval filter may be indicated in pregnant women.…”
Section: Secondary Prophylaxis In Women With Previous Thrombosismentioning
confidence: 99%
“…After therapeutic administration of LMWH for 10-14 days, a prophylactic dose of LMWH should be continued throughout the pregnancy and then replaced with heparin for 6-8 weeks post-partum as described for UFH [140,164,168]. Published studies indicate that the effective maintenance dose of enoxaparin is 40 mg once daily and of dalteparin, 5000 IU once daily [163][164][165][166][167]175,176]. However, in certain thrombophilic conditions these doses should be increased depending on the risk of recurrent VTE.…”
Section: Secondary Prophylaxis In Women With Previous Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Several studies have suggested the safety and efficacy of LMWH during pregnancy. 13,20,21 In addition, the risk of adverse heparin-induced thrombocytopenia and osteoporosis after LMWH treatment is greatly reduced compared with UFH. [20][21][22][23][24][25] In our previous work, we showed that the messenger RNA and protein expression of the proteoglycan decorin (DCN) was reduced in PE-and FGR-affected placentae compared with controls.…”
Section: Introductionmentioning
confidence: 99%